PENGARUH PENYUNTIKAN DOSIS MINIMAL DEPOT MEDROKSIPROGESTERON ASETAT (DMPA) TERHADAP BERAT BADAN DAN KIMIA DARAH TIKUS JANTAN GALUR SPRAGUE-DAWLEY - Yurnadi, Yurnadi; Suryandari, Dwi Anita; Moeloek, Nukman (UI Scholars Hub, 2009)
Effect of Injection Minimal Dosages of Depot Medroxyprogesterone acetate (DMPA) to Body Weight and Blood Chemistry Male Rat Strain Sprague-Dawley. Many family planning program focus more on men. Until now, vasectomy has been the commonly used method for male contraception. However, this method creates inconvenience such as irreversibility and psychological problems. One of the alternatives contraception is the combination of depot medroxyprogesterone acetate (DMPA) and androgen. The minimum dosage of DMPA could suppress testosterone level that leads to reduced spermatogenesis and sperm viability. Nevertheless, until now it is not known whether minimum dosages of DMPA have an effect to body weight and blood chemistry. Therefore, this research aimed at determinate the effect of minimal dosages of DMPA to body mass and blood chemistry using male rats (Rattus norvegicus L.) strain Sprague-Dawley as model. This research using completely randomized design, unequal size sample, castration treatments and several doses DMPA (1.25, 0.625, and 0.313 milligram). Injecting of DMPA conducted intramuscularly on week 0 and week 12. Normality/homogeneity Data normality were analyzed before ANOVA test. Then, abnormal data were tested using Kruskal-Wallis test. The result shows that injection of DMPA in various doses do not have an effect on body weight and blood chemistry such as erytrocytes, haemoglobin, hematocrite, HDL, LDL, total cholesterol, SGOT, SGPT and triglyseride) (p>0,05). Furthermore, it is concluded that that no effect of minimal dosages of DMPA to body mass and blood chemistry of rat.